BIOPROSPECÇÃO DE FUNGOS FILAMENTOSOS PRODUTORES DE XILANASES ISOLADOS DE REMANESCENTES DE FLORESTA OMBRÓFILA MISTA: POTENCIAL XILANOLÍTICO DO FUNGO CA5 - MARTINS, MAÍRA DALVANA (2016)
The use of microorganisms has been a common practice in the field of biotechnology, especially in industrial processes. Therefore, studies aiming the bioprospecting of microorganisms with potential for bioactive compounds production, in particular enzymes, have increased in recent years. Among the enzymes of biotechnological interest, xylanases have been widely studied because of their many economic applications, such as in the pulp and paper industries, production of animal feed, food, textile and others. This study aimed to isolate fungal strains from Araucaria Forest (AF) soil and assess its potential for xylanase production. Additionally, we aimed to explore the effects of various physical and chemical parameters on the production of xylanase by the best xylanase producer strain previously selected, using the passion fruit peel as alternative substrate. In addition, the enzymes produced were biochemically characterized. In xylanases optimization process, the Central Composite Rotational Design applicable to the Response Surface Methodology was employed as a statistical tool. Among the 65 strains isolated from two distinct AF fragments, the CA5 fungus exhibited the higher levels of xylanases, in the presence of passion fruit peel. Maximum production levels were achieved when the concentration of the substrate was 2.9%, the pH of the culture was adjusted to 4.2 and cultivation time was 8.6 days, corresponding to 65.49 U mL-1. The xylanases produced were more active at 60 °C and pH 6.5, remained stable at optimum temperature and at pH 6.0. Under the lasted condition, more than 90% residual activity was observed. In relation to the effect of various substances on the xylanase activity, the enzyme was remarkably stimulated by 10 mM Mn2+ and 2 mM Cu2+, but considerably inhibited in the presence of detergent SDS. The passion fruit peel is a promising substrate for xylanases production, since it is a low cost residue produced in large quantities. The fungus CA5 has demonstrated potential for producing these enzymes, which exhibit desirable properties for certain industrial applications.